2012
DOI: 10.3324/haematol.2011.057653
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C is associated with risk of venous thromboembolism in subjects with normal kidney function - the Tromso study

Abstract: BackgroundPrevious studies have shown an association between impaired kidney function, assessed by cystatin C-based estimated glomerular filtration rate, and venous thromboembolism. The aim of this study was to investigate whether serum cystatin C was associated with a risk of venous thromboembolism among subjects with normal kidney function in a prospective population-based study. Design and MethodsCystatin C was measured in serum from 3251 men and women with normal kidney function, aged 25-84 years, who part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…28,29 In addition, increased cystatin C levels were also correlated with BMI and older age. 19,[30][31][32] The present study also shows that serum cystatin C levels were correlated with age, BMI, Scr, and eGFR in the total population in accordance with other previous reports. D-Dimer is formed when cross-linked fibrin is broken down by plasmin.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…28,29 In addition, increased cystatin C levels were also correlated with BMI and older age. 19,[30][31][32] The present study also shows that serum cystatin C levels were correlated with age, BMI, Scr, and eGFR in the total population in accordance with other previous reports. D-Dimer is formed when cross-linked fibrin is broken down by plasmin.…”
Section: Discussionsupporting
confidence: 95%
“…In a recent article, Brodin et al reported that 61.4% of the 83 patients with VTE had deep vein thrombosis and only 38.6% had PTE. 19 The authors showed that patients with serum cystatin C levels in the top quartile (≥0.87 mg/L) had a 2.5-fold increased risk of VTE compared to those with levels in the bottom quartile (≤0.72 mg/L) adjusted for age, sex, BMI, smoking, diabetes, and high sensitivity (hs)-CRP. 19 In addition, when analyzing cystatin C as a continuous variable, they found that an increase of 1 SD (0.11 mg/L) in cystatin C concentration was associated with a 46% increased risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate risk assessment of an individual's propensity to develop CVDs is essential for personalized health care and primary prevention of these conditions. An increasing number of novel biomarkers have been linked to CVD risk [3][4][5][6][7][8][9][10][11][12][13][14], implying their critical role in precise risk assessment for heterogeneous CVDs. Current established functions for CVD risk stratification are either based only on conventional risk factors or include a limited number of biomarkers [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be hypothesized that increased serum levels of cystatin C represent an inadequate counterbalancing mechanism to avoid thrombosis formation. [11][12][13][14][15][16][17] A recent study conducted by Urbonaviciene et al demonstrated that higher serum cystatin C levels independently predicted 5-year all-cause and CVS mortality in symptomatic peripheral arterial disease patients with normal renal function. In accordance with Urbonaviciene et al 18 Loew and colleagues 19 have reported that only high plasma cystatin C levels(> 1.24 mg/l) were associated with risk of fatal and nonfatal cardiovascular events during the follow-up.…”
Section: Introductionmentioning
confidence: 99%